Analysis of reverse logistics operations for a computer company - Tan, Wee Kwan; Kumar, A.; Sundarakani, B. (IGI Global, 2011)
As reverse logistics is a relatively new field in supply chain management, especially in Asia, a detailed study is conducted to understand the status of companies practicing reverse logistics to support their Asia Pacific operations. This paper discusses an empirical examination of a company performing reverse logistics in Asia with Singapore being the coordination hub with the United States (US). Data on the transaction volumes and other material information are collected over a period of two years to understand the behaviour and trends of reverse logistics in this company. Statistical tools such as serial correlation, seasonality and trend analysis are performed on the data to understand their behaviour and its managerial implication. The study has shown that there is an upward trend for the return volume and how financial closing has an impact to the return volumes.